"Business groups and transnational capitalism in Central America: economic and political strategies", de Benedicte Bull, Fulvio Castellacci y Yuri Kasahara - Robles Rivera, Francisco (Universidad de Costa Rica, 2015)
Reseña del libro "Business groups and transnational capitalism in Central America: economic and political strategies", de Benedicte Bull, Fulvio Castellacci y Yuri Kasahara.